Neuropsychological Assessment of Professional Ice Hockey Players: A Cross-Cultural Examination of Baseline Data Across Language Groups. (2nd January 2020) - Echemendia, Ruben J; Thelen, Joanie; Meeuwisse, Willem; Hutchison, Michael G; Rizos, John; Comper, Paul; Bruce, Jared M
Abstract: Objective: Neuropsychological testing in sports has become routine across all levels of play. The National Hockey League (NHL) has conducted baseline neuropsychological assessment of all players since 1997. This study seeks to examine baseline differences among linguistically and culturally diverse groups within the NHL and to present comprehensive normative data for these groups. Method: Baseline data were obtained from 3, 145 professional hockey players' baseline symptom reporting, neuropsychological test performance on a battery of traditional "paper and pencil" measures, and self-reported concussion history. In addition, 604 baseline post-injury paper and pencil evaluations were conducted the season following a concussion and 4, 780 computerized baseline ImPACT administrations were obtained following the introduction of computerized testing. Results: Normative data for paper and pencil tests and ImPACT are presented for the major language groups within the league: English, French, Swedish, Russian, Czech, Finnish, and German (ImPACT only). It was found that symptom reporting, the number of concussions sustained, and neuropsychological test results vary significantly based on a players' language of origin. This variability was also present when players were tested in their language of origin. Conclusions: This study provides insight into the significant baseline differences that exist among NHL players regarding symptoms, concussion history, and cognitive functioning. The findings are discussed with respect to the evaluation and management of NHL players who sustain concussion and more generally in the context of neuropsychological assessment in cross-cultural settings, including the importance of examining neuropsychological functioning using culturally specific norms.